2014
DOI: 10.1039/c4nr02453b
|View full text |Cite
|
Sign up to set email alerts
|

WS2 nanosheet as a new photosensitizer carrier for combined photodynamic and photothermal therapy of cancer cells

Abstract: We have developed a simple and efficient strategy to fabricate WS2 nanosheets with low toxicity and good water solubility via a liquid exfoliation method by using H2SO4 intercalation and ultrasonication. The as-prepared WS2 nanosheets were employed not only as an NIR absorbing agent for photothermal therapy (PTT) but also as a photosensitizer (PS) carrier for photodynamic therapy (PDT) due to their sheet like structure that offers large surface area to load PS molecules. Moreover, singlet-oxygen generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
199
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(205 citation statements)
references
References 47 publications
5
199
1
Order By: Relevance
“…278 Thanks to their broad light absorption in the visible and near-infrared regions of the spectrum, TMDC nanosheets have been first used as photothermal therapy agents. 283,284 Further studies have also demonstrated their potential as drugs delivery agents, 285,286 using their large surface area to load active molecules. Using direct synthesis pathways, metal-doped WS2 have been prepared to combine magnetic resonance imaging (contrast from the dopant) with X-ray imaging (high Zelements forming the nanosheet).…”
Section: Copyright (2014)mentioning
confidence: 99%
“…278 Thanks to their broad light absorption in the visible and near-infrared regions of the spectrum, TMDC nanosheets have been first used as photothermal therapy agents. 283,284 Further studies have also demonstrated their potential as drugs delivery agents, 285,286 using their large surface area to load active molecules. Using direct synthesis pathways, metal-doped WS2 have been prepared to combine magnetic resonance imaging (contrast from the dopant) with X-ray imaging (high Zelements forming the nanosheet).…”
Section: Copyright (2014)mentioning
confidence: 99%
“…[22] It has also been reported that anticancer drugs can be released from NIR absorbable nanocarriers triggered by laser irradiation because the local hyperthermia could induce increased thermal vibration of polymer chains and weaken the interactions between the drugs and the nanocarriers. [23] We thus measured the DOX release profile with and without NIR laser irradiation for 5 min (808 nm, 1 W cm −2 ). The data in Figure S5 (Supporting Information) revealed that the NIR irradiation can accelerate the release speed of DOX in the first two hours at pH 5.0.…”
mentioning
confidence: 99%
“…S8). Given their two-dimensional nature, 22 we assumed that the large contact area and multivalent effect of the PNs would enhance binding ability, consequently endowing SPNs with a high potential for application in targeted drug delivery.…”
Section: Resultsmentioning
confidence: 99%